Visual discrimination training increases the speed stimulus processing and leads to an earlier onset of stimulus encoding - Camila Bustos; Rodrigo Montefusco-Siegmund; Fernando Peña; María de la Luz Aylwin (PLoS ONE, 2025)
Wide experience with complex visual stimuli results in better performance and faster responses in object discrimination, categorization, and identification through perceptual learning and expertise. Visual experts exhibit an earlier onset of the availability of stimulus information for encoding and a reduction of the encoding duration required for discrimination and individuation. However, it is still unresolved whether perceptual learning and expertise shapes the speed of perceptual processing in the first milliseconds after stimulus onset. Twenty seven participants developed perceptual learning and expertise through discrimination of pairs of Kanji stimuli across six sessions. Discrimination sensitivity was evaluated at four training levels with encoding durations between 17 and 1000 ms. Behavioral results show a gradual increase in sensitivity and a reduction in encoding duration required for a given performance with discrimination training. A shifted exponential function fitted to the sensitivity data revealed that training leads to a faster rate of performance change with encoding durations, suggesting increases in the speed of information extraction, as well as an earlier availability of stimulus information for encoding, suggesting an earlier onset of information extraction. Interestingly, the increase in the rate of performance paralleled that of sensitivity with training, suggesting an association with perceptual learning and expertise. Besides, the earlier availability of stimulus information is achieved after two training sessions, likely reflecting the acquisition of stimuli familiarity. The faster speed of information extraction and the earlier stimulus information extraction for encoding, likely contribute to faster responses and higher performance, typical of perceptual experts in object discrimination and individuation. These findings provide additional evidence for the outcome of discrimination training on stimulus processing in the first milliseconds after stimulus onset.